Politics Of Development And Articulation Of Indigenous Identity: The Formation Of Munda Identity In Barind, Bangladesh - Sharmeen, Shaila
This paper is about the identity formation of an ethnic group – the Munda of Bangladesh. The key issue of this paper is how the Munda identity has been constructed by the state and by the development agencies, covering historical as well as current trends. Throughout colonial and postcolonial periods in the academic and policy discourse, the Munda/Adibashi were represented as "primitive," "backward" and "underdeveloped." Here, I argue that the images contribute to the making of the "category" of Adibashi as "primitive," "backward" or "underdeveloped" are actually a perception, not a representation of reality. The representation of Munda identity articulated by the academician or the development practitioner ignores the complexities, dynamism and history of these people